2012
DOI: 10.1007/s10750-012-1182-1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate warming on the long-term dynamics of key fish species in 24 European lakes

Abstract: 10.1007/s10750-012-1182-1Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. form, nor will it be during the first three months after its submission to Hydrobiologia."Corresponding author: Erik Jeppesen (ej@dmu.dk)We dedicate this paper to the late Prof. Jürgen Benndorf, a true pioneer and mentor in lake and reservoir manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
201
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 253 publications
(213 citation statements)
references
References 144 publications
(128 reference statements)
7
201
0
5
Order By: Relevance
“…The shift from large to small species indicates enhanced fish predation on large-bodied zooplankton [13,60], which coincides well with the increased catches of small planktivorous fish in the lake. Less frequent surveys of other similar Danish shallow lakes have also pointed towards reduced fish size despite nutrient loading reduction and this has been implicated to multiple effects of warming [25]. Accordingly, we found that summer air temperatures, especially in April where fish are spawning, have become warmer in the region during the study period, and the changes were significantly correlated with the abundances of small (positive) and large fish (negative).…”
Section: Discussionsupporting
confidence: 54%
“…The shift from large to small species indicates enhanced fish predation on large-bodied zooplankton [13,60], which coincides well with the increased catches of small planktivorous fish in the lake. Less frequent surveys of other similar Danish shallow lakes have also pointed towards reduced fish size despite nutrient loading reduction and this has been implicated to multiple effects of warming [25]. Accordingly, we found that summer air temperatures, especially in April where fish are spawning, have become warmer in the region during the study period, and the changes were significantly correlated with the abundances of small (positive) and large fish (negative).…”
Section: Discussionsupporting
confidence: 54%
“…The harvest of whitefish Coregonus spp. has declined substantially in Lake Vättern in Sweden and Lake Peipsi in Estonia (Kangur et al 2007;Jeppesen et al 2012). In the UK and Ireland, a decline in the coregonid pollan Coregonus autumnalis in recent decades has been attributed to changes in temperature (Harrod et al 2002).…”
Section: 41mentioning
confidence: 99%
“…A drastic reduction in the population of smelt has occurred in shallow Lake Peipsi as shown from commercial fishing, with the decline particularly strong in years with heat waves (Kangur et al 2007;Jeppesen et al 2012). In contrast, the abundance of eurythermal species, including the thermo-tolerant carp Cyprinus carpio (Lehtonen 1996;Jeppesen et al 2012) is rising in several lakes in the North Sea region .…”
Section: 41mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last 40 years, water temperature has increased by about 1.5°C (Jeppesen et al 2012), and populations of several species including European Whitefish (Thomas et al 2010) and European Perch (Eckmann et al 2006) have changed. Recently, fisheries yields have decreased drastically (Rösch 2014), and in 2015 yield fell by approximately 50% from the already low yield of 2014.…”
Section: Europementioning
confidence: 99%